American Jews explore Israel: Jewish and Israel identity exploration with Harvey Pekar and Sarah Glidden. Issue 5 (2nd November 2019) - Reingold, Matt
ABSTRACT: Sarah Glidden's (2010) Understanding Israel in 60 Days and Harvey Pekar's Not the Israel My Parents Promised Me are analysed as autobiographical texts that suggest different ways that American Jews navigate their identities as Americans, Jews and Zionists. The two works are situated in the larger field of American Jewish authors who use Israel as the setting for their literature. Both Glidden and Pekar develop relationships with Israel that evolve over the course of the work, but they arrive at very different understandings of the country, its morality, and their place within Israel and the Jewish community. Through their personal journeys, each author undergoes a difficult process of discovering Israel before arriving at their new orientation. This suggests that for American Jews, forming a relationship with Israel is a complex process that requires navigation and sacrifice and might even entail alienation and loss.